From dry pressing to plastic forming of ceramics: Assessing the workability window. (20th November 2018) - Schiavo, Lícia S.A.; Mantas, Pedro Q.; Segadães, Ana M.; Cruz, Robinson C.D.
Graphical abstract: Highlights: Ceramic powders can be shaped only while in the funicular state. Dry pressing is effective above the pendular-to-funicular state transition. The workability window for plastic forming begins at maximum particle packing. The workability window extends to the funicular-to-capillary state transition. Dried body density can be used to quantitatively define the workability window. Abstract: The shaping water content in clay-based ceramic building materials has conflicting implications in shaping and drying, decisively contributing to the cost-effectiveness of the industrial process. This work addresses the long-standing difficulties related to the quantification of the workability window for plastic forming. From uniaxial compression stress-strain curves, the yield stresses of mixtures of a red-firing clay and a ground basalt rock with different moisture contents were obtained. Combination of those results with the wet and dried bodies densities, showed that ceramic powders can be shaped only while in the funicular state: for this clay, dry pressing is effective above the pendular-to-funicular transition (∼5.7 wt% moisture) and the workability window for plastic forming begins at the maximum dried body density, which signals the transition from open-to-closed gas pores in the funicular state (∼15 wt% moisture), and extends to the funicular-to-capillary transition (∼18 wt% moisture). Drying did not alter the moist particle structure, which enables the expeditious determination of the workability window from dried body density and initial moisture content.